Auxiliary ECR heating system for the gas dynamic trap - Shalashov, A.G.; Gospodchikov, E.D.; Smolyakova, O.B.; Bagryansky, P.A.; Malygin, V.I.; Thumm, M. (Вопросы атомной науки и техники, 2012)
Physics aspects of a new system for electron cyclotron resonance heating (ECRH) at the magnetic mirror device Gas Dynamic Trap (GDT, Budker Institute, Novosibirsk) are discussed. This system based on two 400 kW / 54.5 GHz gyrotrons is aimed at increasing the electron temperature up to the range 250…350 eV for improved confinement. The key issue of the GDT conditions is that conventional ECRH geometries are not accessible. The proposed solution is based on a peculiar effect of radiation trapping in inhomogeneous magnetized plasma. Under specific conditions oblique launch of gyrotron radiation results in right-hand-polarized electromagnetic waves propagating with high n|| in the vicinity of the cyclotron resonance, what provides effective single-pass absorption of the injected microwave power. Обсуждаются физические аспекты и возможные параметры новой системы дополнительного ЭЦР-нагрева для газодинамической магнитной ловушки ГДЛ (ИЯФ, Новосибирск). При использовании излучения двух 400 кВт / 54.5 ГГц гиротронов можно ожидать повышения температуры электронов до 250…350 эВ и улучшения времени удержания ионов. Трудности, связанные с невозможностью использования традиционных схем ЭЦР-нагрева в геометрии ГДЛ, предлагается преодолеть за счет эффекта захвата излучения, вводимого из вакуума в виде необыкновенной волны под определенным углом, в трехмерно-неоднородной магнитоактивной плазме. Обговорюються фізичні аспекти і можливі параметри нової системи додаткового ЕЦР-нагріву для газодинамічної магнітної пастки ГДП (ІЯФ, Новосибірськ). При використанні випромінювання двох 400 кВт/54.5 ГГц гіротронів можна чекати підвищення температури електронів до 250…350 еВ і поліпшення часу утримання іонів. Труднощі, пов'язані з неможливістю використання традиційних схем ЕЦР-нагрівання в геометрії ГДП, пропонується подолати за рахунок ефекту захоплення випромінювання, що вводиться з вакууму у вигляді незвичайною хвилі під певним кутом, в тривимірно-неоднорідній магнітоактивній плазмі.